2020
DOI: 10.4103/sjg.sjg_558_19
|View full text |Cite
|
Sign up to set email alerts
|

EncephalApp Stroop App predicts poor sleep quality in patients with minimal hepatic encephalopathy due to hepatitis B-induced liver cirrhosis

Abstract: Background/Aim: A novel computerised Stroop test- EncephalApp Stroop App (EncephalApp) has good diagnostic validity for minimal hepatic encephalopathy (MHE) in cirrhotic patients. The Stroop test is correlated with sleep disturbances which are common, and severely affects health-related quality of life in cirrhotic patients with MHE. We evaluated the relationship between sleep quality and EncephalApp results in patients with MHE due to hepatitis B-induced liver cirrhosis. Patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…That led them to conclude that the EncephalApp had good sensitivity in diagnosing minimal HE. Lou et al 16 assessed the EncephalApp from a different perspective and found that the use of the mobile app could predict poor sleep quality in patients with cirrhosis secondary to hepatitis B, with good sensitivity and specificity for diagnosing minimal HE (85.2% and 77.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…That led them to conclude that the EncephalApp had good sensitivity in diagnosing minimal HE. Lou et al 16 assessed the EncephalApp from a different perspective and found that the use of the mobile app could predict poor sleep quality in patients with cirrhosis secondary to hepatitis B, with good sensitivity and specificity for diagnosing minimal HE (85.2% and 77.3%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In practice, the prevalence of MHE varies between 30% and 70% and is suspected in cirrhotic patients who have abnormalities on psychometric testing, particularly impaired attention and reaction speed [ 130 ]. It has also been demonstrated that PHES score is significantly correlated with PSQI and ESS scores in a study conducted among 100 patients with cirrhosis [ 34 ].…”
Section: Assessment Of Sleep Disorders In Patients With Cldmentioning
confidence: 99%